Early childhood exposure to secondhand smoke and behavioural problems in preschoolers. Issue 1 (December 2018) - Luk, Tzu; Wang, Man; Suen, Yi; Koh, David; Lam, Tai; Chan, Sophia
Abstract Evidence on behavioural abnormalities in children exposed to secondhand smoke is limited. This study examined the relation between infant/ toddler cotinine concentration, a biomarker of secondhand smoke exposure, and behavioural problems in preschoolers who were unexposed to maternal smoking during gestation. A prospective cohort of 301 non-smoking mothers with their young children aged ≤18 months visiting postnatal primary care clinics in Hong Kong was enrolled in 2012 and followed by telephone survey 3 years afterwards. Saliva was collected at baseline for cotinine assay. Child behavioural health at 3-year follow-up was assessed by the parent-reported Strengths and Difficulties Questionnaire (SDQ). We conducted multivariable linear regressions to compute regression coefficients (b ) of SDQ scores in relation to salivary cotinine level. Mean ± SD age of children at follow-up was 3.7 ± 0.5 years and 50.8% were boys. After adjusting for age, sex, birthweight, household income, housing type, maternal education and depressive symptoms, greater cotinine concentrations during early childhood were associated with greater conduct problems (b  = 0.90, 95% CI 0.03–1.76) and hyperactivity/ inattention (b  = 1.12, 95% CI 0.07–2.17) at preschool age. This study corroborates previous findings on the potential role of secondhand smoke in development of child behavioural problems.